Implementation of Ethno-Edugames Application to Improve Student Learning Outcomes - Novita Permata Sari; Kartika Pertiwi Ratna; Anggi Tias Pratama (Postgraduate, University of Mataram, 2025)
The writing of this article aims to present the results of the analysis in the form of a literature review on the results of research on the implementation of the ethno edu games application to improve student learning outcomes. The ethno-edugames application is an educational game with the concept of local wisdom in the form of traditional games packaged into an application on a smartphone as a learning medium. The articles used consist of 4 research articles from national and international journals. The research procedure used in writing this article with 5 steps of literature review, determining the research theme, namely the implementation of the ethno edu games application to improve student learning outcomes, searching for and collecting various articles on the sinta website, google scholar, and other websites, classifying various types of articles that are relevant to the research theme, synthesizing relevant articles by marking important points in each article; and writing articles from the results of the synthesis. The conclusion of this article is that the use of ethno-edugames media in learning has succeeded in improving student learning outcomes. Ethno-Edugames that have succeeded in improving learning outcomes are, hopscotch, bebetengan, and Snakes and ladders.